IPTEKS PENGENDALIAN INTERN SIMDA KEUANGAN DALAM PENGELOLAAN DATA KEUANGAN PADA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI SULAWESI UTARA - Polii, Imanuel Ronaldo Angelo; Pontoh, Winston (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
As a government agency, Local Development Planning Agency (BAPPEDA) of North Sulawesi Province is a Local Government Work Unit (SKPD) that has the task of helping the Governor in terms of planning and execution of regional policies. In order to create good regional financial management, BAPPEDA of North Sulawesi Province implements Financial SIMDA in its financial data management system. Financial SIMDA is an application developed by BPKP to facilitate local government in implementing good regional financial management. The use of Financial SIMDA produces output in the planning, administration, accounting and reporting processes. Therefore, the implementation of Financial SIMDA in BAPPEDA of North Sulawesi Province has made financial management easier, so it needs to be monitored and improved. An internal control is needed to guarantee the quality of information from the output produced by Financial SIMDA. There are several elements of application internal control that must be applied, which includes: boundary controls, input controls, process controls, output controls.Keywords: Internal control, Financial SIMDA, Financial data management